Dynamic Analysis of Rotor Speed and Electrical Torque of Brushless Doubly Fed Induction Generator (BDFIG) Under Symmetrical and Unsymmetrical Faults - Mahmoudi, Javad; Moussavi, Seyed Zeinolabedin; Mahmoodi, Esmail (Journal of Technology Innovations in Renewable Energy, 2014)
The brushless doubly fed induction generator (BDFIG) has the potential to be employed as a variable speed wind turbine generator. Owing to brushless configuration of this generator, its reliability is higher than DFIG. Most of the grid faults are unsymmetrical. Hence, this paper analyzes dynamic behavior of BDFIG under symmetrical and unsymmetrical faults and presents dynamic models for both fault types. In order to validate the results of analysis, simulations have been carried out using MATLAB/Simulink software. Then, the control winding (CW) current is compared under symmetrical and unsymmetrical faults.